The centrality of a peripheral cosmopolitanism: the "Collection of Great Social Scientists” in Brazilian social sciences (1978-1990) - Rodrigues, Lidiane Soares (2018)
Research on the international circulation of knowledge has shown that countries dominated in the economic and political space are prone to the practice of importing goods from dominant countries also on a symbolic level. However, they do not do this, passively or randomly; but according to structuring principles of its own internal cultural market. Adopting this perspective, the present work will deal with the “Collection Great Social Scientists”, published by the “Ática” publisher, between 1978 and 1990, and coordinated by the sociologist Florestan Fernandes (1920-1995). The article will describe the collection, make a sociogenesis of the publisher, characterize the negotiations prior to the authors’ choice to compose it, and, finally, situate the agents involved in the space of Brazilian Social Sciences, reconfigured during the 1970s.